Structure and organization of the chicken H2B histone gene family. - Grandy, D K (1987)
The results of Southern blotting experiments confirm that the chicken H2B histone gene family contains eight highly homologous members. One or two more sequences which are considerably divergent from the others appear to exist in the chicken genome. Seven of the eight H2B genes have been cloned and sequenced. All seven genes fall in two histone gene clusters, but no common arrangement exists for the clusters themselves. Three different H2B protein variants are encoded by these seven genes. The nucleotide sequence homology among the genes within their coding sequences appears to exceed that required for the corresponding protein sequences, suggesting that histone H2B mRNA sequence and structure are both selected during evolution. An analysis of the 5' flanking sequence data reveals that these genes possess CCAAT and TATA boxes, elements commonly associated with genes transcribed by RNA polymerase II. In addition, these genes all share an H2B-specific element of the form: ATTTGCATA. The 3' sequences of these genes contain the hyphenated symmetrical dyad homology and downstream purine-rich sequence shared by histone genes in general.